Atividade biocida de óleos essenciais in vitro e em matriz alimentar láctea sobre Staphylococcus aureus e Listeria monocytogenes - Salimena, Alessandra Pereira Sant'anna (2010)
The Minas cheese is quite consumed primarily by their availability in retail outlets, affordable, high performance, simple processing of the final product, enabling fast return on investment and increase of income in family production units. Microbiological research conducted with Minas cheese has allowed the isolation of many pathogens of importance in public health from this product, which at different times causing several damages to the food industries. To ensure the reduction of spoilage microorganisms and potential pathogens present in foods, preservatives are utilized to consumer health. In recent years, growing consumer demand for natural products free of synthetic preservatives, has led the food industry to incorporate natural preservatives in food products. The use of natural antimicrobial compounds have the advantage of being more accepted by consumers, since they are considered 'non-chemical'. This work was conducted in order to determine the yield and chemical composition of essential oils of Syzygium aromaticum, Origanum vulgaris, Ocimum basilicum, Salvia officinalis and Pimpinella anisum; determine the antibacterial activity of these oils on Staphylococcus aureus ATCC 25923 and Listeria monocytogenes ATCC 19117; determine Minimum Inhibitory Concentration (MIC) of essential oils on S. aureus and L. monocytogenes and determine the effect of essential oil of S. aromaticum on the growth of S. aureus and L. monocytogenes inoculated in dairy food matrix. The extraction of essential oils was performed by hydrodistillation using a Clevenger aprelho modified. The antibacterial effect of different concentrations of pure essential oils was analyzed by agar diffusion. The MICs found for the bacterium S. aureus were (v/v): S. aromaticum (1,56%), O. vulgare (3,12%), S. officinalis and O. basilicum (12,50%) and the essential oil of P. anisum MIC was 25,00%. For L. monocytogenes MICs of the values found were (v/v): S. aromaticum (0,78%), O. vulgare (3,12%), O. basilicum (25,0%) and essential oils of S. officinalis and P. anisum showed no antimicrobial activity against the bacteria at concentrations tested. Given the importance of studying new substances capable of controlling the growth and presence of S. aureus and L. monocytogenes in food industry, has been added the essential oil that showed the greatest inhibition zone (S. aromaticum) in the dairy food matrix. The dairy food matrix without the addition of microorganisms with only the addition of cultures of S. aureus and L. monocytogenes were the controls used. Counts were performed in micro-aerobic mesophilic, S. aureus, L. monocytogenes, coliforms and thermotolerant, ensuring that only the inoculated microorganisms were present in the mass. The pots containing the dairy food matrix were stored in an environmental chamber at 7°C throughout the experiment. The physicochemical characteristics of the mass of cheese were determined after compression of the mass, including moisture, fat, acidity, pH and ash. The analysis of dairy food matrix presented within the Brazilian standards. The essential oil of Syzygium aromaticum test on pathogenic bacteria S. aureus at concentrations of 0,78%, 1,56% and 3,12% and L. monocytogenes at concentrations of 0,39%, 0,78% and 1,56% in inoculated dairy food matrix, showed excellent antibacterial activity over the concentrations tested.